Hubungan ASI eksklusif dengan kejadian stunting pada balita 6-24 bulan pada tiga kecamatan kasus tertinggi stunting di Kabupaten Jeneponto, Sulawesi Selatan - Rambu, Sitti Herliyanti; Ilyas, Asmiana Saputri (EcoVision: Journal of Environmental Solutions, 2024)
Background: Stunting is a major issue with toddlers' eating habits, which are frequently linked to malnutrition during these crucial early years of development. The World Health Organization (WHO) defines stunting as a developmental failure characterized by a body length deficit about age, specifically a z-score of less than -2. A persistent problem with public health in some communities is the high rate of stunting. A few elements add to hindering, with selective breastfeeding being a basic determinant. Hindering, or weakened direct development, is a typical wholesome issue among babies that influences long-haul well-being, mental turn of events, and future efficiency. This study looks to evaluate whether selective breastfeeding is a gamble factor for hindering kids between the ages of 6 and two years in the Jeneponto region. Methods: An observational research design with a case-control approach was used. Children aged 6 to 24 months who were recorded in the posyandu (community health post) toddler register across three sub-districts—West Bangkala, Bontoramba, and Rumbia—were chosen for their high stunting rates. Findings: The review uncovered that 39.67% of kids were solely breastfed, while 60.33% were not. Bivariate examination demonstrated a remarkable connection between restrictive breastfeeding and hindering in this age bunch (p = 0.03; OR = 1.74), recommending that non-only breastfed youngsters had a 1.74 times higher gamble of hindering contrasted with the people who were solely breastfed. In any case, multivariate examination, which represented factors, for example, kid age, birth weight, mother's level, and breastfeeding status, uncovered that the connection between restrictive breastfeeding and hindering was as of now not huge (p = 0.49; OR = 1.23). This suggests that when these extra factors are thought of, the gamble of hindering non-solely breastfed youngsters was just 1.23 times higher than in only breastfed kids, a distinction not measurably huge. Conclusion: Although the initial data indicate that not exclusively breastfeeding increases the risk of stunting by 74%, this risk is reduced when other factors like maternal height, child age, birth weight, and overall breastfeeding status are taken into consideration. This demonstrates the complexity of stunting and the need for comprehensive interventions that address breastfeeding practices as well as broader factors affecting the health of mothers and children.